Incorporating green and sustainable remediation analysis in coal combustion residuals (CCR) surface impoundment closure decision making. Issue 4 (September 2017) - Boroumand, Ali; Greenberg, Grace; Herman, Kurt; Lewis, Ari
Abstract: In response to new coal combustion residuals (CCR) disposal regulations, many coal‐fired utilities have closed existing unlined surface impoundments (SIs) that were traditionally used for disposal of CCR. The two primary closure options are closure‐in‐place (CIP), which involves dewatering and capping, and closure‐by‐removal (CBR), which includes excavation, transportation, and disposal of the CCR into a lined landfill. This article provides a methodology and a case study of how green and sustainable remediation concepts, including accounting for the life cycle environmental footprints and the physical risks to workers and community members, can be incorporated into the closure decision‐making process. The environmental impacts, occupational risks, and traffic‐related fatalities and injuries to workers and community members were calculated and compared for closure alternatives at a hypothetical site. The results demonstrated that the adverse impacts of the CBR option were significantly greater than those of the CIP option with respect to the analyzed impact pathways.